2020
DOI: 10.2196/18074
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Feedback of Electronic Medication Adherence Products: Qualitative Analysis

Abstract: Background Medication management among older adults continues to be a challenge, and innovative electronic medication adherence products have been developed to address this need. Objective The aim of this study is to examine user experience with electronic medication adherence products, with particular emphasis on features, usefulness, and preferences. Methods Older adults, caregivers, and health care provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 61 publications
1
22
0
1
Order By: Relevance
“…Our previous research regarding the user experience of MAPs has shown that portability is a feature that users consider when choosing a product for their medication management needs. 15 Similar results were shown by a qualitative study regarding patients’ views about electronic adherence devices. This study reported that patients preferred products that were lightweight and smaller in size due to the fact that they were more convenient to carry around.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our previous research regarding the user experience of MAPs has shown that portability is a feature that users consider when choosing a product for their medication management needs. 15 Similar results were shown by a qualitative study regarding patients’ views about electronic adherence devices. This study reported that patients preferred products that were lightweight and smaller in size due to the fact that they were more convenient to carry around.…”
Section: Discussionsupporting
confidence: 73%
“…13 Twenty-one products were randomly selected to assess their usability, workload and user experience. 14 , 15 We found significant difference in usability and workload of products among a participant population of older adults, caregivers and health care providers. 14 We also concluded that product features such as the ability to store multiple medications, portability, reminder and alarm functions, among others, can be of significant importance for older adults.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…A study discussing user's perspectives on adherence products has cited similar results. The study reported that patients prefer to use an adherence product for their medication management if it provides them with a feeling of less worry and sense of assurance that they did not miss any doses [57].…”
Section: Plos Onementioning
confidence: 99%
“…Faisal et al [ 46 ] and Ahmad et al [ 47 ] examined user experience with electronic medication adherence products. Both studies have demonstrated that these products have potential to promote independent medication management in older adults.…”
Section: Medication Aidsmentioning
confidence: 99%